Investigating the Implementation of Block System Learning Model at Higher Education during the Covid-19 Pandemic - Nur Salam (STAI Hubbulwathan Duri, 2022)
This study aims to investigate the management and learning achievement in vocational higher education using the block system learning model. This study used the descriptive qualitative method. The subjects consisted of 150 students, 6 lecturers for courses, and 6 structural officials, while the object of the research is learning management using the block system learning model. The data was collected using observations, interviews, documentation, and questionnaires. The steps in analyzing data are processing, reducing, presenting, and drawing conclusions. The results of the study state that; 1) in the planning of the block system learning model, lecturer involvement is needed for curriculum design 2) the implementation of the block system learning model is prioritized to be implemented in one course; 3) the assessment system is in accordance with the provisions set out in the curriculum evaluation; 4) the institution provides flexibility in developing learning curriculum in accordance with the Indonesian Qualifications Framework and Indonesian National Work Competency Standards. The inhibiting factors with the block system learning model are the disruption of software and hardware facilities; 5) the achievement target of student competence is by what has been determined by the curriculum.